Chest Computed Tomography Findings of Eight Patients With Covid-19 Diagnosis: Case Series - Ozkan, Seda; Tutar, Onur; Akdeniz, Yonca Senem; Cakmak, Fatih; Ipekci, Afsin; Biberoglu, Serap (Acta Biomedica Atenei Parmensis, 2021)
COVID-19 is an infectious disease caused by the virus named severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) and declared a pandemic on March 11, 2020, by the world health organization. In Turkey, the first cases began to appear on March 11, 2020. After the cases in China, the appearance of ground glass with or without consolidation in the posterior and periphery of the bilateral lung is determined as the main finding of COVID-19. In this article, we wanted to share the tomography findings of eight patients who were diagnosed with COVID-19 in our emergency department and who had lung involvement.